2019
DOI: 10.1002/pd.5572
|View full text |Cite
|
Sign up to set email alerts
|

DiGeorge syndrome chromosome region deletion and duplication: Prenatal genotype‐phenotype variability in fetal ultrasound and MRI

Abstract: Objective The aim of the study was to assess genotype‐phenotype correlation of prenatally diagnosed fetal DGS and dup22q11 syndrome by fetal molecular genetic analysis, fetal ultrasound, and/or MRI. Methods In this retrospective consecutive case series, pregnant women were screened for fetal anomalies during a period of 10 years. Fetal genotype was assessed in 72 cases upon the occurrence of five prenatal fetal phenotypic features: cardiac anomalies, hypo/aplastic thymus, craniofacial malformations, urinary ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Fetal MRI can be a helpful tool, e.g., when evaluating the fetal brain, heart, or thymus. Two studies noted its role in the evaluation of the fetal thymus [8,64]. Fetal MRI has been found to be effective in the assessment of fetal cardiac anatomy, particularly for a more accurate study of the arch vessels [65].…”
Section: Third-trimester Ultrasoundmentioning
confidence: 99%
“…Fetal MRI can be a helpful tool, e.g., when evaluating the fetal brain, heart, or thymus. Two studies noted its role in the evaluation of the fetal thymus [8,64]. Fetal MRI has been found to be effective in the assessment of fetal cardiac anatomy, particularly for a more accurate study of the arch vessels [65].…”
Section: Third-trimester Ultrasoundmentioning
confidence: 99%
“…In a study on 10 fetuses, diagnosed with DiGeorge syndrome prenatally, IUGR was detected in one fetus. 17 Another study on 42 cases with confirmed 22q11.2 deletion syndromes did not find any indication of IUGR. 18…”
Section: Discussionmentioning
confidence: 93%
“…Fetal MRI can aid in evaluating the fetal brain or thymus 62,84,85 . Availability of fetal MRI is limited, however, and its use is generally reserved for diagnostic clarification in centers with experience.…”
Section: Introductionmentioning
confidence: 99%